Pengaruh Positif Kegiatan CSR (Corporate Social Responsibility) Bagi Kesejahteraan Masyarakat di Lingkungan Perkebunan Kelapa Sawit di Sei Daun - Lubis, Muhammad Kamil; Zebua, Yuniman; Nasution, Meisa Fitri (Jurnal Ekonomi, Akutansi dan Manajemen Nusantara, 2026)
The palm oil plantation sector is one of the strategic industries that significantly contributes to Indonesia’s economy; however, its presence often generates social and environmental impacts on surrounding communities. Therefore, the implementation of Corporate Social Responsibility (CSR) serves as an essential instrument for companies to fulfill their social obligations while maintaining harmonious relations with local communities. This study aims to analyze the positive impact of CSR programs on community welfare in the palm oil plantation area of Sei Daun Village. The research employs a descriptive qualitative approach supported by quantitative data obtained through questionnaires. Data were collected from local communities, village officials, and company representatives through interviews, observations, documentation, and questionnaires distributed to 100 respondents. The findings indicate that CSR programs have a positive influence on improving community welfare, particularly in economic conditions, education, health services, and infrastructure development. Furthermore, CSR initiatives contribute to strengthening social relations between the company and the community and reducing potential social conflicts. This study is expected to provide both academic and practical insights for companies in designing and implementing more effective, sustainable, and targeted CSR programs within the palm oil plantation sector.